2018
DOI: 10.1111/bph.14372
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of hydrogen sulfide with disulfides: formation of a stable trisulfide and implications for biological systems

Abstract: In aqueous systems, the reaction between H S and RSSR results in the formation of equilibria whereby H S, RSH, RSSR, RSSH and RSSSR are present. In a biological system, any of these species can be responsible for the observed biological activity. These equilibrium species can also be generated via the reaction of RSH with RSSSR. Due to these equilibria, Cys-SSS-Cys can be a method for generating any of the other species. Importantly, HEK293T cells treated with Cys-SSS-Cys results in increased levels of hydrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 39 publications
6
91
1
Order By: Relevance
“…We here would like to refer the reader to our companion paper, where we demonstrated that Equilibrium 15 is indeed likely to prevail in cellular systems. We found that cysteine trisulfide (Cys‐SSS‐Cys) provide a useful pharmacological tool because treatment of cells with this dialkyl trisulfide results in high intracellular levels of hydropersulfides (due to a shift towards the backward reaction of Reaction ), which protected HEK293T cells from electrophilic stress (Bianco et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…We here would like to refer the reader to our companion paper, where we demonstrated that Equilibrium 15 is indeed likely to prevail in cellular systems. We found that cysteine trisulfide (Cys‐SSS‐Cys) provide a useful pharmacological tool because treatment of cells with this dialkyl trisulfide results in high intracellular levels of hydropersulfides (due to a shift towards the backward reaction of Reaction ), which protected HEK293T cells from electrophilic stress (Bianco et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…[18] In actual cellular systems the presence of free cysteine should facilitate interconversion of these species and they likely work collectively to exert the functions of H 2 S( or H 2 S n and persulfides). [18] In actual cellular systems the presence of free cysteine should facilitate interconversion of these species and they likely work collectively to exert the functions of H 2 S( or H 2 S n and persulfides).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It should be noted that in this work we mainly focused on the ability of these compounds to scavenge H 2 S, not other H 2 S-related sulfur species,s uch as H 2 S n and persulfides.I ti s known that H 2 S-producing enzymes (CBS,C SE, 3MST,a nd CARS) also produce H 2 S n and persulfides and they are in equilibrium in biological systems. [18] In actual cellular systems the presence of free cysteine should facilitate interconversion of these species and they likely work collectively to exert the functions of H 2 S( or H 2 S n and persulfides). In fact, we observed that sulfonyl azides reacted with cysteine persulfide, albeit at markedly slower rates compared to its reaction with H 2 S (Figure 5d).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It should be noted that in this work we mainly focused on the ability of these compounds to scavenge H 2 S, not other H 2 S‐related sulfur species, such as H 2 S n and persulfides. It is known that H 2 S‐producing enzymes (CBS, CSE, 3MST, and CARS) also produce H 2 S n and persulfides and they are in equilibrium in biological systems . In actual cellular systems the presence of free cysteine should facilitate interconversion of these species and they likely work collectively to exert the functions of H 2 S (or H 2 S n and persulfides).…”
Section: Figurementioning
confidence: 99%